PENGELOLAAN PERSEDIAAN PADA APLIKASI SAKTI MENGGUNAKAN ALGORITMA FIRST IN FIRST OUT (FIFO) - Hafez Aditya; M Ardiansyah; Sidik Sidik; Windu Gata (IIB Darmajaya, 2020)
Not only in the private sector (private), in a government agency (public sector) also known management of goods supplies to support the operation of the government agencies. As we know, for an agency the diamond does not know the profit/loss. However, with the management of supplies goods in a government agency need to also be managed properly, so as to get optimal results and can reduce the operational costs. During this time in many government agencies, the budget is financed from the NATIONAL budget, for the management of these supplies there is no definite pakem. In this study will demonstrate the algorithms used in the software of the institution level financial Application System (SAKTI) developed by the Directorate General of Treasury of the Ministry of Finance which is the method of valuation of FIFO supplies to achieve optimum management of inventory.